Modifikasi Kurikulum bagi Anak Slow Learner Terindikasi Tunagrahita di SDIT Permata Hati - Laily Nurmalia; Radiatul Fitri; Qarina Utami Frinardi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Curriculum modification is essential in inclusive schools because students with diverse cognitive and adaptive abilities cannot always achieve common learning targets through uniform instruction. This study aimed to describe curriculum modification for two slow learners indicated as having intellectual disability at SDIT Permata Hati, Bekasi. A qualitative case-study design was employed from May to June 2025. Data were collected through classroom observation, semi-structured interviews with the principal, a classroom teacher, and a special education teacher, as well as documentation of learning programs and student progress. Data analysis followed the interactive stages of reduction, display, and conclusion drawing. The findings show that the school modified four curriculum elements: learning objectives, content, methods or processes, and assessment. The modification was operationalized through an Individual Learning Program, lowered and simplified indicators, concrete and visual media, repeated instruction, additional learning time, individual sessions in the inclusion room, and participation in regular-class projects. Teacher collaboration, parent involvement, training, and supporting facilities strengthened implementation. The modified curriculum enabled students to participate more meaningfully, although achievement remained individual and required continuous assistance. The study implies that inclusive curriculum modification should be systematic, flexible, and supported by coordinated school resources.